Hidroponik dalam Konsep Urban Farming Hasilkan Produk Sayur Sehat - Nofrianil; Fedri Ibnusina; Alfikri; John Nefri; Arnayulis; Darnetti; Rachmad Fadillah (PADMA, 2026)
The concept of urban farming by using limited land in urban home gardens as agricultural land for vegetable production supports community food independence. Agricultural technology with a hydroponic cultivation system is a solution for producing healthy vegetables without chemical pesticides. The advantage of hydroponics is producing vegetables intensively. The aim of the service activity is to understand how to consume vegetables without chemical pesticides to support a healthy lifestyle and independence for urban communities in agricultural production using hydroponics. The implementation method is the extension method in the form of healthy food material without pesticides, urban farming material with hydroponic technology and demonstration methods for hydroponic vegetable cultivation. The activity was carried out in Tiakar Village, Payakumbuh City. The results of the activity obtained an increase in the percentage of community understanding of the importance of a healthy lifestyle by consuming food free from chemical pesticides, the community was able to practice cultivating healthy vegetables without chemical pesticides using hydroponic technology after being provided with education by the team.